Answer:
-2
Step-by-step explanation:
as x goes up 1 y goes down 2
slope is change in y over change in x
-2/1=-2
Answer:
x = -2, y = -2
Step-by-step explanation:
Your goal is to try and cancel out a variable. I want to get rid of y so i subtracted the first equation from the second one.
After that I solve for x and got x=-2.
I used x=-2 and plugged it back into either of the equation to solve for y.
Answer:
3x-2
Step-by-step explanation:
-2x-2+5x=-2x+5x-2=3x-2
X= -1 and -11
Put -1 and -11 in for x. The answer comes out 6